Upper-limb bone mineral density of female collegiate gymnasts versus controls - Proctor, K. L.; Adams, W. C.; Shaffrath, J. D.; van Loan, M. D. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: We examined bilateral bone mineral density (BMD) in the arms of female college gymnasts to assess the relative contribution of high-impact loading forces versus daily activities on bone plasticity. METHODS: Twenty-five female collegiate gymnasts and 25 controls were studied. BMD of the lumbar spine, proximal femur, and whole body were assessed via dual energy x-ray absorptiometry. Upper-limb BMD was determined by custom analyses of the whole-body scans to examine arms individually. RESULTS: BMD of gymnasts was significantly (P < 0.0001) greater than controls at all sites. Whole-body BMD was 8% higher in gymnasts (1.270 +/- 0.078 vs 1.175 +/- 0.073 g x cm(-2)), with 18-19% differences in the lumbar spine (1.427 +/- 0.144 vs 1.212 +/- 0.106 g x cm(-2), right proximal femur (1.298 +/- 0.101 vs 1.100 +/- 0.129 g x cm(-2)), and left proximal femur (1.293 +/- 0.111 vs 1.104 +/- 0.133 g x cm(-2)). Arm BMD was 17% greater in gymnasts, with higher values in both dominant (1.013 + 0.067 vs 0.875 + 0.066 g x cm(-2)) and nondominant (1.002 + 0.060 vs 0.849 + 0.062 g x cm(-2)) arms. Intragroup comparisons revealed a significantly (P < 0.0001) greater BMD in the dominant arm of the controls but no side-to-side difference in the arms of the gymnasts. CONCLUSIONS: Upper-limb BMD followed use patterns in both gymnasts and controls, demonstrating that the forces imposed on the arms with gymnastics training enhanced BMD and resulted in no bilateral differences. These findings illustrate the association between gymnastics training and increased BMD throughout the body, suggesting that the high BMD values observed in gymnasts are due primarily to the activity itself rather than selection bias.